The awareness on global and national issues: the comparison study between Bachelor in Information Studies and Bachelor in Administration Studies students in UiTM Kedah. / Nurzafirah Nasirdin - Nasirdin, Nurzafirah (Faculty of Information Management, 2010)
The study is carried out to discover about awareness of students towards global and national issues. Thus, this study is to evaluate and identify student's awareness of global and national aspect issues that would lead students in better performance in their future career and lifestyle. Awareness of the global and national issues will enable students to develop their attitudes, knowledge, skills and more understand of political, economic and social problems of the global and national issues. Thus it will change the perception on dependency on any kinds of issues. Bachelor in Administration Studies (BAS) students and Bachelor in Information Studies (BIS) students of UiTM Kedah are the respondents of the research to be study.